2003
DOI: 10.2460/ajvr.2003.64.166
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of morphine and isoflurane in horses

Abstract: Our results do not support routine clinical use of MOR administered IV at dosages of 0.25 or 2.0 mg/kg as an adjuvant to anesthesia in horses administered ISO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
101
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 20 publications
2
101
2
1
Order By: Relevance
“…Opioids have been reported to induce central nervous system excitation and subsequent locomotor activity [6]. In another study, the behavioral characteristics of a horse recovering from general anesthesia after administration of a high dose of morphine were clearly not desirable [18]. In the present study, such adverse effects were not observed in Group SF, and the qualities of the recoveries were clinically acceptable.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Opioids have been reported to induce central nervous system excitation and subsequent locomotor activity [6]. In another study, the behavioral characteristics of a horse recovering from general anesthesia after administration of a high dose of morphine were clearly not desirable [18]. In the present study, such adverse effects were not observed in Group SF, and the qualities of the recoveries were clinically acceptable.…”
Section: Discussionsupporting
confidence: 51%
“…A reduction in the minimum alveolar concentration (MAC) of inhalant agents after administration of various drugs is often used as a measure of analgesia in both humans and animals [11,14,18]. In this study, a reduction of about 13% in the sevoflurane requirement was observed in horses administered fentanyl as part of the anesthetic regimen.…”
Section: Discussionmentioning
confidence: 65%
“…The excitement that occurred in one horse from the remifentanil group was mild, lasted only a short time, and was considered clinically insignificant. In addition, individual animal variability, the potential for opioids cause sympathetic stimulation in horses [13,20], might help explain this finding.…”
Section: Discussionmentioning
confidence: 98%
“…The MAC reduction in horses after administration of opioids has been disappointing compared with other species. In dogs, 2 mg/kg morphine (IV) resulted in an isoflurane MAC reduction of 50% [25], whereas the same dose in horses resulted in MAC reduction in some horses and an increase in others, along with an undesirable recovery from anesthesia [13]. Alfentanil reduced the MAC of isoflurane in cats [26] but did not alter the MAC of halothane in horses [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation